(untitled) (Research, Society and Development, 2021)
Oral health is part of physical and mental health, as it interferes with both chewing and digestion and the possibility of communication. The aim of this study was to identify the oral health conditions of patients admitted to a psychiatric institution and to discuss implications for psychosocial rehabilitation processes. The study was carried out with 104 patients, using the odontogram and individual semi-structured interview for data collection. Quantitative data were analyzed using descriptive statistics and the DMFT index. The results included absolute and relative frequencies and measures of central tendency. Qualitative data were treated using the content analysis technique. The results showed an average DMFT index of 19.41 for men and 20.38 for women and total loss of teeth of 29% in women and 6.06% in men. Two categories emerged from the content analysis: "Total absence of teeth (edentulous) interfering with communication" and "Absence of teeth and self-image/aesthetics". It is concluded that the relationship between oral health and psychosocial rehabilitation strategies needs to be considered during the therapeutic process by the multidisciplinary team.